BPIFB2 is highly expressed in "cold" lung adenocarcinoma and decreases T cell chemotaxis via activation of the STAT3 pathway. (April 2022) - Zhang, Jingwen; Ping, Yu; Zhao, Qitai; Guo, Ru; Shan, Jiqi; Liu, Fengsen; Wang, Jia; Zhang, Yi
Abstract: Background: Studies have shown that patients with lung adenocarcinoma exhibit a poor prognosis, and the overall effective rate of immunotherapy is relatively low. Previous studies reported on the BPIFB2 gene have shown that it participates in immune regulation in gastric cancer; however, the role and mechanisms of BPIFB2 in lung cancer remain unclear. The present study evaluated the mechanism of BPIFB2 in lung adenocarcinoma. Methods: First, the immune infiltration status of lung adenocarcinoma was analyzed by performing bioinformatics analysis and the BPIFB2 gene was screened. Expression of BPIFB2 in lung adenocarcinoma was studied in vitro, and it was confirmed that BPIFB2 exerted effects on the chemotaxis of tumor cells to T cells. The mechanism was further analyzed and verified via in vivo experiments. Finally, the molecular mechanism of the effect of BPIFB2 on tumor cell chemotaxis T cells was confirmed in clinical specimens. Results: Patients with lung adenocarcinoma presented with different degrees of immune cell infiltration, wherein the tumor tissue exhibiting a low infiltration of CD8+T cells was defined as a cold tumor, demonstrating a high expression of BPIFB2. In vitro experiments revealed that although the knockdown of BPIFB2 exerted no significant effect on the proliferation and apoptosis of tumor cells, it could significantly increase the number of T cells presenting with chemotaxis in lung adenocarcinoma cells, and this might be attributable to a decrease in STAT3 activation and an increase in CCL5 expression after BPIFB2 knockdown. In vivo experiments showed that after BPIFB2 knockdown, the expression of CCL5 increased in tumor cells and the recruitment of T cells increased by tumor cells. It was also confirmed that the expression of BPIFB2 was negatively correlated with CCL5 expression in clinical specimens. Conclusion: Our study indicated that BPIFB2 was highly expressed in patients presenting with a cold tumor of lung adenocarcinoma. BPIFB2 knockdown increased the expression of CCL5 and the number of chemotactic CD8+T cells in lung adenocarcinoma. BPIFB2 may thus be considered an important target for immunotherapy. Highlights: BPIFB2 was highly expressed in "cold tumors" of lung adenocarcinoma. Knockdown of BPIFB2 activated the STAT3 pathway and increased CCL5 expression. Knockdown of BPIFB2 increased the number of chemotactic CD8 + T cells.